The chromatin fiber: multiscale problems and approaches. (April 2015) - Ozer, Gungor; Luque, Antoni; Schlick, Tamar
Abstract : Highlights: Review of DNA compaction in silico on multiple spatial and temporal scales. Survey of chromatin models, with emphasis on combining experiment and theory. Perspective on multiscale challenges in chromatin organization. Proposal for novel multiscale approaches connecting atomistic to nuclear scales. Abstract : The structure of chromatin, affected by many factors from DNA linker lengths to posttranslational modifications, is crucial to the regulation of eukaryotic cells. Combined experimental and computational methods have led to new insights into its structural and dynamical features, from interactions due to the flexible core histone tails or linker histones to the physical mechanism driving the formation of chromosomal domains. Here we present a perspective of recent advances in chromatin modeling techniques at the atomic, mesoscopic, and chromosomal scales with a view toward developing multiscale computational strategies to integrate such findings. Innovative modeling methods that connect molecular to chromosomal scales are crucial for interpreting experiments and eventually deciphering the complex dynamic organization and function of chromatin in the cell.